The Effect of Health Education on Handwashing Behavior and Wearing Masks for Traders in the Market - Farida Farida (CV. Global Health Science Group, 2020)
Washing hands with soap is also known as an effort to prevent disease. This is done because hands are often agents that carry germs and cause pathogens to pass from one person to another either by direct contact or indirect contact. While the use of masks is part of a comprehensive series of prevention and control measures that can limit the spread of certain viral respiratory tract diseases, masks can be used either for healthy people (used to protect themselves when in contact with infected people) or to control sources ( used by an infected person to prevent further transmission). This study aims to analyze the effect of health education on hand washing behavior (6 steps) and the use of masks for traders in the Trenggalek Bendo market. Methods: The study was conducted in February 2022. The design of this study was a one group pre test post test design. The population of this research is all traders of Bendo market, Trenggalek Regency, the sample is 30 traders with purposive sampling technique. The independent variable is health education and the dependent variable is the effect of hand washing (6 steps) and the use of masks. Data collection with questionnaire sheets. Data collection techniques using editing, coding, scoring, tabulating and statistical tests using the Wilcoxon test. Results: The results of the study of 30 respondents, before being given heath education about 6 steps of hand washing and wearing masks, most of the traders behaved negatively, namely those who behaved negatively with ctps as many as 24 people (80%) and the behavior of wearing masks was negative 22 people (73.3%). Meanwhile, after being given health education, most of the traders who had positive handwashing behavior were 22 people (73.3%) and 25 people (83.3%). Statistical test shows p value = 0.000 < (0.05) so that H0 is rejected or H1 is accepted. Conclusion: There is an effect of health education on hand washing behavior (6 steps) and the use of masks for traders at the Bendo Trenggalek market.